2018
DOI: 10.1007/s11103-018-0723-z
|View full text |Cite
|
Sign up to set email alerts
|

A tandem array of UDP-glycosyltransferases from the UGT73C subfamily glycosylate sapogenins, forming a spectrum of mono- and bisdesmosidic saponins

Abstract: This study identifies six UGT73Cs all able to glucosylate sapogenins at positions 3 and/or 28 which demonstrates that B. vulgaris has a much richer arsenal of UGTs involved in saponin biosynthesis than initially anticipated. The wild cruciferous plant Barbarea vulgaris is resistant to some insects due to accumulation of two monodesmosidic triterpenoid saponins, oleanolic acid 3-O-β-cellobioside and hederagenin 3-O-β-cellobioside. Insect resistance depends on the structure of the sapogenin aglycone and the glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…Similarly, members of the UGT72 subfamily have been shown to function in flavonol (Yin et al, 2017), flavanone, anthocyanin (Zhao et al, 2017) and monolignol glucosylation (Lim et al, 2005;Lanot et al, 2006) and are probably involved in lignin biosynthesis . Members of the UGT73 subfamily catalyzed the 3-O-glucosylation of the sapogenins oleanolic acid and hederagenin (Augustin et al, 2012;Erthmann et al, 2018) and the modification of the brassinosteroid phytohormones (Poppenberger et al, 2005), while UGT73C6 transferred glucose from UDP-glucose to the 7-OH position of kaempferol 3-O-rhamnoside and quercetin 3-O-rhamnoside, respectively (Jones et al, 2003) and UGT73B3 and UGT73B5 are implicated in the modification of salicylic acid and scopoletin (Simon et al, 2014). Therefore, in agreement with published data, UGT71, 72 and 73 from N. benthamiana glucosylated phenolic compounds, including flavonols, but also produced glucosides from aliphatic alcohols such as terpenoids (Table 1).…”
Section: In Silico Analysis and Substrate Screeningmentioning
confidence: 99%
“…Similarly, members of the UGT72 subfamily have been shown to function in flavonol (Yin et al, 2017), flavanone, anthocyanin (Zhao et al, 2017) and monolignol glucosylation (Lim et al, 2005;Lanot et al, 2006) and are probably involved in lignin biosynthesis . Members of the UGT73 subfamily catalyzed the 3-O-glucosylation of the sapogenins oleanolic acid and hederagenin (Augustin et al, 2012;Erthmann et al, 2018) and the modification of the brassinosteroid phytohormones (Poppenberger et al, 2005), while UGT73C6 transferred glucose from UDP-glucose to the 7-OH position of kaempferol 3-O-rhamnoside and quercetin 3-O-rhamnoside, respectively (Jones et al, 2003) and UGT73B3 and UGT73B5 are implicated in the modification of salicylic acid and scopoletin (Simon et al, 2014). Therefore, in agreement with published data, UGT71, 72 and 73 from N. benthamiana glucosylated phenolic compounds, including flavonols, but also produced glucosides from aliphatic alcohols such as terpenoids (Table 1).…”
Section: In Silico Analysis and Substrate Screeningmentioning
confidence: 99%
“…The P450s CYP716A80 and CYP716A81 from the G-type and P-type, respectively, are preferentially expressed in the G-type and oxidises b-amyrin at the C-28 position to oleanolic acid, the precursor of hederagenin (Khakimov et al, 2015). Several UDP-glycosyltransferases from the UGT73C subfamily in B. vulgaris have been isolated (Augustin et al, 2012;Erthmann et al, 2018). Among these, UGT73C11 and its orthologues UCT73C10 have evolved to specifically catalyse 3-O-glucosylation of sapogenins (triterpenoid saponin backbones), including oleanolic acid and hederagenin.…”
Section: Introductionmentioning
confidence: 99%
“…This biocatalyst is separated from the other sequences in the phylogenetic tree (Supplemental Figure S5) and shows a preference for ring glucosylation (Table 1) Further studies demonstrated that members of the UGT72 family glucosylate flavonols (Yin et al 2017), flavanones, anthocyanins (Zhao et al 2017), and monolignols (Lanot et al 2008) and are most probably involved in lignin biosynthesis (Wang et al 2012). UGT73 family members catalyze the 3-O-glucosylation of the sapogenins oleanolic acid and hederagenin (Augustin et al 2012;Erthmann et al 2018) as well as the conversion of brassinosteroid phytohormones . UGT73 enzymes are also responsible for the 7-O-glucosylation of kaempferol and quercetin 3-O-rhamnoside (Jones et al 2003), the transformation of salicylic acid and scopoletin (Simon et al 2014) as well as feruloyl tyramine (Sun et al 2019).…”
Section: Identification Of Unprecendented C 13 -Apocarotenol Ugtsmentioning
confidence: 99%